Distributed adaptive bit-loading for spectrum optimization in multi-user multicarrier systems - Jagannathan, Sumanth; Cioffi, John M. (Physical communication, 2008)
This paper presents a low-complexity discrete bit-loading algorithm for multi-user multicarrier systems with application to spectrum balancing in digital-subscriber-lines. The algorithm can be implemented in a distributed manner using limited information that is sent to modems by a spectrum management center (SMC). The SMC classifies users in the network as strong or weak, based on their channel and noise conditions. Weak users execute a discrete bit-loading algorithm approximating water-filling, such as the Levin–Campello (LC) algorithm, while strong users use a rate-penalty table along with a modified LC algorithm to limit their interference to weak users. Simulation results show that the proposed algorithm can achieve near-optimal performance. In addition, polite bit and gain adaptation algorithms are developed using the structure of the proposed bit-loading algorithm, which enables easy and fast adaptation to channel and noise variations.